Amended description of Amphilophium pilosum (Bignoniaceae), a species from Megamexico - Rios-Méndez, Monzerrath; Martínez-Domínguez, Lilí; Nicolalde-Morejón, Fernando (Instituto de Ecología, A.C., 2022)
Background and Aims: Amphilophium is a genus of Neotropical lianas belonging to the family Bignoniaceae, with a diversity of 47 species. Four species occur in Megamexico, which are morphologically characterized by hexagonal stems and capsular fruits with convex valves. The recent collections of Amphilophium in Veracruz state (Mexico) led to the identification of A. pilosum, previously reported only from Honduras. The present study aims to amend the morphological description and broaden the known distribution extension of A. pilosum. Methods: Botanical material of Amphilophium pilosum from the dry forest of the central region in Veracruz State (Mexico) was collected and herborized. The population localized in the municipality Actopan was periodically visited to record the phenology of the species. Herbarium specimens of Amphilophium paniculatum throughout its distribution range, which is the most related species in morphological and phylogenetic terms, deposited in national and foreign herbaria, were examined in physical and digital collections. In addition, for comparative purposes, the specimens of all species of the genus with distribution in Megamexico were reviewed. Key results: An amended description of Amphilophium pilosum is presented, accompanied by a complete illustration that includes the fruit for the first time, as well as details about the character states considered diagnostic for this species. Additionally, we include a dichotomous key and distribution maps for Amphilophium species distributed in Megamexico. Conclusions: Mexico represents the northernmost country where Amphilophium pilosum is located. The record of this species increased the diversity of the genus Amphilophium in Mexico to five species, which highlights the importance of the taxonomic studies that focus on the biological diversity.